2017
DOI: 10.1021/acs.biomac.7b00356
|View full text |Cite
|
Sign up to set email alerts
|

Block-Sequence-Specific Glycopolypeptides with Selective Lectin Binding Properties

Abstract: Glycopolypeptides with defined block sequences were prepared by sequential addition of two different N-carboxyanhydrides (NCAs), followed by selective deprotection and functionalization of pre-defined positions within the polypeptide backbone. The sequential arrangement of the galactose units and the block sequence length have been systematically varied. All the glycopolypeptides have been obtained with a similar overall composition and comparable molecular weights. Circular dichroism measurements revealed som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 47 publications
0
39
0
2
Order By: Relevance
“…Due to the difficulty of obtaining a homogeneous form of glycoproteins, synthetic mimics of glycoproteins, such as glycopolymers, are generally utilized to study the interactions between carbohydrates and lectins . The ability of glycopolymers to interact with lectins was found to be greatly influenced by many factors, such as the rigidity of the polymer, the density of sugar molecules, polymer molecular weight and polymer architectures . For example, Kobayashi et al synthesized rigid cylindrical phenyl isocyanide glycopolymers and compared their lectin‐binding behaviour with flexible phenylacrylamide glycopolymers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the difficulty of obtaining a homogeneous form of glycoproteins, synthetic mimics of glycoproteins, such as glycopolymers, are generally utilized to study the interactions between carbohydrates and lectins . The ability of glycopolymers to interact with lectins was found to be greatly influenced by many factors, such as the rigidity of the polymer, the density of sugar molecules, polymer molecular weight and polymer architectures . For example, Kobayashi et al synthesized rigid cylindrical phenyl isocyanide glycopolymers and compared their lectin‐binding behaviour with flexible phenylacrylamide glycopolymers .…”
Section: Introductionmentioning
confidence: 99%
“…7 The ability of glycopolymers to interact with lectins was found to be greatly influenced by many factors, such as the rigidity of the polymer, the density of sugar molecules, polymer molecular weight and polymer architectures. [8][9][10][11][12] For example, Kobayashi et al…”
mentioning
confidence: 99%
“…To check such possibilities, pH dependent CD spectra of PU‐PP‐1 were monitored (Figure a). At pH 10, the CD spectrum showed a maximum ellipticity at λ =218 nm and minimum ellipticity at λ =190 nm indicating random coil conformation of PU‐PP‐1 . Whereas at pH 4.5, the polypeptide chains adopted a α‐helical conformation, as indicated by the two ellipticity minima at λ =208 and 222 nm.…”
Section: Resultsmentioning
confidence: 95%
“…While this capacity to control cell organization has previously been demonstrated with peptide functionalized aligned fiber polymers, this is the first time that a synthetic glycopolymer has been shown to exhibit the same effect on cell attachment. Previous studies have demonstrated that synthetic glycopolymers can interact specifically with human C‐type lectins and the sequence of sugar moieties diversifies the specific interaction, potentially explain this promising cell–material interaction. However, the mechanisms by which tenocytes interact with glycopolymers needs to be addressed by further study.…”
Section: Resultsmentioning
confidence: 99%